Antidiabetic Effects of Aloe Vera Whole Leaf Extract and Sitagliptin in Streptozotocin-induced Diabetic Rats - Sobia Javaid , Akbar Waheed, Sobia Javaid , Akbar Waheed (Journal of Rawalpindi Medical College, 2020)
Introduction: Aloe Vera, a perennial herb, is being used since ancient times for the cure of various diseases and is recently being used in curing diabetes due to the synergistic activity of its over 75 biologically active ingredients. The objective of the study was to compare the antidiabetic effects of Aloe Vera whole leaf extract with standard antidiabetic drug Sitagliptin on streptozotocin-induced diabetic rats. Material and Methods: The present study was RCT, conducted at the Department of Pharmacology, Islamic International Medical College, Rawalpindi in collaboration with the National Institute of Health, Islamabad, Pakistan, from September 2019 to August 2020. A total of 40, young Sprague Dawley rats weighing between 220-250 grams were taken and randomly divided into Group A (Normal Control) and group B. After induction of Type-2 Diabetes, group B was further subdivided into 3 groups with 10 rats each: Group B1 (Diabetic Control), Group B2 (Aloe Vera whole Leaf Extract treated), GROUP B3 (Sitagliptin treated). Terminal Sampling was done to measure FBS and HbA1c on Day 60. Statistical Analysis was done by applying SPSS version 25. A one-way ANOVA test was used for assessing any difference in the mean values. Post-hoc Turkey analysis was conducted to compare any inter-group mean differences. P-value of <0.05 was considered significant. Results: On completion of the study, at Day 60, mean FBS values for Rats in Group A were 82.40 mg/dl, for Group B1 498.40 mg/dl, for Group B2 89.30 mg/dl, and Group B3 93.00 mg/dl respectively. Mean HbA1c results for rats after terminal sampling in Group A were 3.71%, Group B1 11.84%, Group B2 4.02%, B3 3.73%. Rats in each of Group B2 (Aloe Vera whole leaf treated) and Group B3 (Sitagliptin treated) had a significant reduction in fasting blood sugar and HbA1c levels in comparison to Group B1 (diabetic control), with no statistically significant intergroup differences in results of Group A, Group B2 and Group B3. Conclusion: Aloe Vera whole leaf extract significantly decreased fasting blood glucose and HbA1c levels with almost similar efficacy to Sitagliptin in diabetic rats.